Occurrence of Postural Low Back Pain in Association with Physical Inactivity among Bank Officers of Faisalabad: Postural Low Back Pain in Association with Physical Inactivity - Zahid, Hamza; Ahmad, Danyal; Arshad, Areeba; Sarfraz, Ramish; Altaf, Faiza; Khalid, Amna (Pakistan Journal of Health Sciences, 2023)
The quality of life for several bank officials around the world is impacted by postural low back discomfort. Prescription drugs and over-the-counter analgesics are the two main forms of treatment. Objectives: To assess the prevalence of postural low back pain and its association with inactivity among Faisalabad bank employees. Methods: A purposive sample was drawn from the community of bankers for this cross-sectional survey, which also included a consent form. The data were gathered using the JOABPEQ, or Japanese Orthopaedic Association Back Pain Evaluation Questionnaire. We computed the sample size for our study and employed a purposive sampling technique. The study had 164 participants in total (Faisalabad bank officers). For analysis, chi-square was used. The coded data were entered using the statistical package for service solution (SPSS V-16). Results: The findings revealed that there was a 75% incidence of postural low back pain and frequency was 74.5 among Faisalabad bank personnel. Findings showed that p < 0.05 for postural low back pain and physical inactivity which means there is an association exists between variables. Conclusions: The majority of bank officers do not adjust their posture, and there is no substantial relationship between gender and posture change. The majority of bank officers experience low lumber pain, although there is no discernible link between gender and low lumber pain, as it affects both men and women equally. Majority of the bank officers do not leave their chair and walk during their working hours so, there is significant association between the lower lumber pain and inactivity.